2018
DOI: 10.1371/journal.pone.0197594
|View full text |Cite
|
Sign up to set email alerts
|

Hypergravity enhances the therapeutic effect of dexamethasone in allergic asthma and rhinitis animal model

Abstract: We investigated whether the therapeutic effects of dexamethasone for allergic asthma and rhinitis were enhanced in mice when exposed to hypergravity. Forty mice were divided into 5 groups (n = 8/group): Control group received saline intraperitoneally (i.p.) and intranasally (i.n.); Asthma group received i.p./i.n. ovalbumin (OVA) for inducing allergic asthma/rhinitis; Dexa group received i.n. dexamethasone (0.75 mg/kg) 30 minutes before each OVA challenge; Hypergravity group was subjected to allergic asthma/rhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The dexamethasone treatment did not reduce the levels of IgE and IgG2a, suggesting that the sakuranetin treatment was more effective for the sensitization compared to DX. Similar data was demonstrated by Jang et al in 2018, who showed that DX treatment did not reduce the levels of the OVA-specific IgE antibody [36]. Sakuranetin treatment also reduced the thymus and spleen hypertrophy, suggesting that it suppresses the immune response.…”
Section: Discussionsupporting
confidence: 84%
“…The dexamethasone treatment did not reduce the levels of IgE and IgG2a, suggesting that the sakuranetin treatment was more effective for the sensitization compared to DX. Similar data was demonstrated by Jang et al in 2018, who showed that DX treatment did not reduce the levels of the OVA-specific IgE antibody [36]. Sakuranetin treatment also reduced the thymus and spleen hypertrophy, suggesting that it suppresses the immune response.…”
Section: Discussionsupporting
confidence: 84%
“…At present, the role of inhaled corticosteroids in asthmatic airway remodeling has received increasing attention. 12 Studies have found that glucocorticoid dexamethasone can inhibit ASMC proliferation. 13 Some scholars have found that dexamethasone can alleviate the symptoms of allergic asthma rats.…”
Section: Discussionmentioning
confidence: 99%
“…Although GC therapy is commonly applied in allergic airway inflammation, such as asthma and allergic rhinitis, some limitations of GCs still exist; for example, the current guidelines on dosing vary between countries, and side effects should not be ignored [19]. To maximize therapeutic effects while minimizing potential side effects, combination therapies with GCs have been explored, including other drugs [14], supplementary measures such as hypergravity [20] and nutrients [15]. Among these options, dietary nutrients might be the most convenient and safe.…”
Section: Discussionmentioning
confidence: 99%